Proximity ligation assay to study TSH receptor homodimerization and crosstalk with IGF-1 receptors in human thyroid cells - Krieger, Christine C.; Boutin, Alisa; Neumann, Susanne; Gershengorn, Marvin C. (Frontiers in Endocrinology, 2022)
Proximity ligation assay (PLA) is a methodology that permits detection of protein-protein closeness, that is, proteins that are within 40 nanometers of each other, in cells or tissues at endogenous protein levels or after exogenous overexpression. It detects the protein(s) with high sensitivity and specificity because it employs a DNA hybridization step followed by DNA amplification. PLA has been used successfully with many types of proteins. In this brief review, we will describe the workings of PLA and provide examples of its use to study TSH receptor homodimerization in primary cultures of human thyrocytes, and TSH/IGF-1 receptor crosstalk in Graves’ orbital fibroblasts.